Konstrukční úprava těhlice osobního vozidla - Coufal, Jiří (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2013)
Tato diplomová práce se zabývá konstrukční úpravou konkrétní těhlice v závislosti na změně brzdiče za nesériový. Je zaměřena na tvorbu a následnou úpravu 3D modelu vycházejícího z rozměrů a tvaru reálné těhlice získaných pomocí 3D skenu. Pro upravovanou část je provedena pevnostní kontrola pomocí MKP a výsledky jsou porovnány s hodnotami původní těhlice.

This master´s thesis deals with design modification of specific upright in response to exchange the caliper for non-series one. It focuses on the creation and subsequent adjustment of the 3D model based on obtained size and shape of real upright by using 3D scan. For the editing part is conducted the strength test by using FEM and the results are compared with the values of the original upright.
Design modification of the vehicle upright
Keywords: Těhlice; brzdový třmen; reverzní inženýrství; ATOS; 3D model; MKP; Upright; caliper; reverse engineering; ATOS; 3D model; FEM